StoryBranding : creating standout brands through the power of story - Signorelli, Jim. (Austin, Tex. : Greenleaf Book Group Press, 2012)
"To help brands resonate with their audiences, the author takes you step by step through StoryBranding's six Cs--a process that shows how to approach the development of all brand communications the way story writers approach their characters, plots, and themes."--Jacket.
The birth of a notion -- Storybranding -- Collecting the backstory -- Characterizing the brand -- Characterizing the prospect -- Connecting the characters -- Confronting the obstacles -- Completing the storybrief -- Telling the story.
Includes bibliographical references (pages 229-230).
Keywords: Branding (Marketing); Marketing; Branding (Marketing); Marketing; Marknadsföring